THE INFLUENCE OF RECRUITMENT AND PLACEMENT ON EMPLOYEE PERFORMANCE AT PT. BANK KALTENG WITH COMPENSATION AS MEDIATION - Vivi Pancasari Kusumawardani; Rini Rahmawati; Hastin Umi Anisah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
PT. Bank Kalteng is one of the regional development banks that plays a crucial role in supporting economic growth in Central Kalimantan. The recruitment and placement processes of employees are crucial factors determining the effectiveness and efficiency of the bank's operations. In addition to recruitment and placement, compensation also plays a significant role in determining employee performance. This study aims to evaluate the impact of recruitment and placement on employee performance at PT. Bank Kalteng, with compensation as a mediating variable. The results indicate that recruitment and placement together significantly influence employee performance through the mediation of compensation. Recruitment also directly influences employee performance significantly with compensation as a mediator, as does placement. The analysis results show a path coefficient value of 0.196, a T-statistic value of 4.588, and a P-value of 0.022, indicating that the first hypothesis is accepted. This means that recruitment and placement together significantly affect employee performance through compensation mediation. These findings underscore the importance of effective recruitment and placement roles as well as adequate compensation in enhancing employee performance.